2011
DOI: 10.1103/physrevb.83.174204
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced strain glass to martensite (R) transition in a Ti50Ni44.5

Abstract: Strain glass (STG) in Ni-rich binary Ti-Ni possesses an R-like (rhombohedral) local strain order, but it transforms into B19' martensite under stress. It remains a puzzle why the local strain order in STG yields a different long-range strain order.Here, we systematically investigated a ternary Ti 50 Ni 44.5 Fe 5.5 STG, which exhibited the same STG features as the binary STG, and the local strain order is also an R-like one.Being different from the binary STG, under stress this ternary STG transforms into a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…According to the alculations and Although the β-martensite transformation in Ti alloy is dependant on the stability of β phase, it is also dependant on the formation of martensite. Previous reports [34][35][36] showed that the addition of Co or Mn to Ti alloy forms the formation of point defects and local stresses which suppress the formation of long range ordered martensites and even form glass state instead of martensitic phase. According to the Fleischer theory, the local stress resulted from alloying elements can be expressed as AG c…”
Section: Resultsmentioning
confidence: 99%
“…According to the alculations and Although the β-martensite transformation in Ti alloy is dependant on the stability of β phase, it is also dependant on the formation of martensite. Previous reports [34][35][36] showed that the addition of Co or Mn to Ti alloy forms the formation of point defects and local stresses which suppress the formation of long range ordered martensites and even form glass state instead of martensitic phase. According to the Fleischer theory, the local stress resulted from alloying elements can be expressed as AG c…”
Section: Resultsmentioning
confidence: 99%
“…This is a glassy state of local strain order, being analogous to the ferroelectric relaxor. Similar to the external‐field‐induced relaxor to normal ferroelectric transition, a stress‐induced transition from strain glass to long‐range strain‐ordered martensite has also been found in strain‐glass alloys .…”
Section: External‐field‐induced Transition From Glassy State To Long‐mentioning
confidence: 75%
“…Strain glass was recently found in several ferroelastic/martensite alloys by introducing point defects beyond a critical value . This is a glassy state of local strain order, being analogous to the ferroelectric relaxor.…”
Section: External‐field‐induced Transition From Glassy State To Long‐mentioning
confidence: 98%
“…. In recent years, a new glass state was observed in some martensitic and ferroelastic systems, including the widely used Ni–Ti , Ni–Ti–Fe , Ti–Pd–Cr , and Ni–Co–Mn–Ga . The strain glass state, considered to be a conjugate state to the martensite and ferroelastic state, has features of all glass behaviours such as dynamic freezing, ergodicity breaking and existence of local strain .…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray diffraction (XRD) investigations show there is no average structure change or macroscopic symmetry change during the strain glass transition . Several transmission electron microscopy (TEM) investigations have been carried out in order to reveal the details of the strains, however, so far these have only revealed the existence of nanodomains or diffuse superlattice scattering in electron diffraction patterns, without providing true structural detail at the atomic level .…”
Section: Introductionmentioning
confidence: 99%